Stress, itch, and scratch. (1st April 2019) - Mochizuki, H.; Lavery, M.J.; Nattkemper, L.A.; Albornoz, C.; Valdes Rodriguez, R.; Stull, C.; Weaver, L.; Hamsher, J.; Sanders, K.M.; Chan, Y.H.; Yosipovitch, G.
Summary: Patients with atopic dermatitis (eczema) often report that stress is a major factor to worsen their itchy skin. This study investigated the effects of acute stress on itch, urge to scratch, and scratching behavior in subjects with atopic dermatitis compared to healthy controls. Stress was created in a standardized way using the Trier Social Stress Test (TSST), where subjects were asked to perform a public speaking task and mental arithmetic. In a second control visit, instead of being stressed, subjects watched a non‐stressful video of landscape scenes. Both subjects with atopic dermatitis and healthy subjects reported feeling stressed after the TSST. Interestingly, atopic dermatitis subjects who were more sensitive to stress also had higher eczema severity. Before and after the TSST or landscape video, cowhage (a plant that causes itch) was applied to the arm of each subject. Patients with atopic dermatitis reported less itch from cowhage and less urge to scratch after they had been stressed by the TSST. However, despite reporting less itch, they actually scratched their limbs significantly more when they were stressed. Healthy individuals did not have any difference in itch, urge to scratch, or scratching behavior in the stressful condition compared to the control landscape video condition. This study shows that acute stress can affect itch and scratching differently in chronic itch patients compared to healthy individuals. Stress led to more scratching in those with atopic dermatitis. Over time, this response to stress could lead to increased skin damage from scratching and therefore worse eczema and itch.